Value Chain and Industry 4.0: A Learning from Sritex Experience - Hani Sirine; Roos Kities Andadari (International Journal of Business Studies, 2020)
The implementation of 'Industry 4.0' brings consequences to industry, market and economy, including Textile and Textile Products which is one of the leading sectors in Indonesian export products. The use of more efficient technologies into alternatives that need to be developed to encourage increased productivity and investment in the TPT industry sector. Sritex as one of the fastest growing textile companies has also implemented Industry 4.0. In this research, will be analyzed about the Sritex value chain, the application of Industry 4.0 on the Sritex value chain, and the impact of the application of the Industry 4.0. The type of this research is qualitative research, where data obtained through secondary data contained in company profile, annual report Sritex, and articles related to Sritex. The result of this research is the application of Industry 4.0 technology in the Sritex value chain affecting products and processes, and enabling increased efficiency and productivity of the company. Application of Industry 4.0 affects 3 (three) interactive components of the organization and is highly interdependent, among them technology, structure, and people along the Sritex value chain.